If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = 8 + 6x Solving 56 = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 56 + -6x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 56 + -6x = 8 + 0 56 + -6x = 8 Add '-56' to each side of the equation. 56 + -56 + -6x = 8 + -56 Combine like terms: 56 + -56 = 0 0 + -6x = 8 + -56 -6x = 8 + -56 Combine like terms: 8 + -56 = -48 -6x = -48 Divide each side by '-6'. x = 8 Simplifying x = 8
| 2x^2+7=67 | | 13.6b=100(56278000) | | 0.33y=6 | | x^2+25=100 | | p(x)=-.04x^2+80(x)-1600 | | x^2-4=80 | | 6x^2=10 | | 9(6.2884)=4x | | px=-.04x^2+80x-1600 | | 9x^2=4x^2+100 | | 2x+5=5x+45 | | 5x^2-40=100 | | X^2+49=196 | | x^2-6x+9=2x+6 | | 3(5r+40)=15(3r-24) | | x=3.51-1.9 | | 3x-5=5+7x | | 5x-(x+6)=32 | | 4(2.2-1)-0.8d=23 | | 3x^2-6=34-2x^2 | | 9p-29=16+4p | | 2r-28=-40+4r | | 6(3+5x)-5=193 | | 8x^2-6x^2=54 | | 2x^2-30=70 | | 3x^2+4x^2=35 | | p=4g+4u | | h+5=9h | | 4x^2+17x-79=-2 | | 5a^2+4a-1=0 | | X^2-25=25 | | -9=-7+x+2 |